Europe and the International Division of Labour : new patterns of trade and investment with developing countries - Stevens, Christopher; Verloren van Themaat, Joan. (London : Hodder & Stoughton in association with the Overseas Development Institute and the Institute of Development Studies, 1987)
This volume of the survey begins with a set of broad analysis covering changes in the pattern of interdependence in trade policy by the joint editors and Jacques Pelkmans. These are followed by chapters on foreign investment (Sheila Page) Southern enlargement of EEC (Stefan A. Musto), prospects for African, Caribbean, Pacific (APC) country export (Matthew McQueen and Robert Read) Lome Conventions (Joanna Moss and John Ravenhill) EEC-ASEAN relations, (Rolf J Langhammer) and finally relations with the Organization of Petroleum Exporting Countries (P. Aarts, G. Eisenloeffel and M. Renner)
Includes index.
rpm 11/04/2018
Loans
Keywords: Foreign economic relations; Developing countries; Europe